Modeling ecosystem services in Armenia using InVEST: a scenario-based approach with NextGISWeb integration for public awareness and engagement - E. Kazakov; E. Bukvareva (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
This study explores the application of the open-source InVEST (Integrated Valuation of Ecosystem Services and Tradeoffs) tool to model ecosystem services in Armenia, utilizing a scenario-based approach. By simulating three hypothetical scenarios, where all natural terrestrial land cover classes are replaced with bare ground or croplands, and the reverse scenario replacing anthropogenic areas with grasslands, the study emphasizes the critical role of terrestrial ecosystems in ecosystem service provisioning. The results are published through Web GIS platforms powered by open-source framework NextGIS Web, providing an interactive medium for engaging civil society and fostering public awareness. This integration of advanced modeling techniques with accessible web-based dissemination aims to influence strategic policy-making in forest management, water resource allocation, and urban planning. The findings highlight the potential of scenario analysis and Web GIS to support sustainable development by illustrating the value of ecosystem services to both policymakers and the public.